Leadership in Times of Crisis: Strategies for Guiding Teams Through Adversity - Islomova Sevinch Botirjon qizi (Web of Journals Publishing, 2023)
This article delves into the complex realm of leadership during times of crisis, emphasizing the importance of effective strategies for guiding teams through adversity. It explores the unique challenges that leaders face in turbulent times and examines key leadership approaches and qualities that can inspire resilience, unity, and progress within teams. By drawing insights from real-world examples and research, this study offers a comprehensive understanding of the pivotal role that leadership plays in navigating crises and fostering a collective spirit of determination and hope.
Keywords: Leadership, Crisis Management, Team Guidance, Resilience, Adversity, Strategies.